Preoperative evaluation of basal free triiodothyronine in patients undergoing coronary artery bypass grafting surgery. Does it help? - Tiwari, Kaushal Kishore; Cerillo, Alfredo Guiseppe; Storti, Simona; Bevilacqua, Stefano; Clerico, Aldo; Iervasi, Giorgio; Glauber, Mattia (Journal of College of Medical Sciences-Nepal, 2015)
no Background & Objectives: The postoperative Low T3 syndrome has been considered as a possible source of reduced myocardial contractility, resulting in increased mortality after CABG. Effect of preoperative Low T3 has not been well studied in patients undergoing CABG surgery. Aim of our study is to evaluate effect of preoperative Low T3 syndrome in patients undergoing CABG surgery. Materials & Methods: Six hundred and six patients undergoing CABG were included in this prospective study. The impact of the base-line FT3 concentration and of preoperative low T3 syndrome on the risk of postoperative low cardiac output and hospital death was analyzed. Results: Fifteen patients (2.3%) postoperatively and 159 (26.2%) developed major complications. At univariate analysis a reduced EF, the presence of peripheral vascular disease, the NYHA class, the surgical urgency, the aortic cross-clamp time, the CPB time and the FT3 concentration at admission were significantly associated with low CO and higher mortality. At multivariate analysis, the CPB time, an emergency procedure, a reduced LVEF, and the fT3 concentration were independently related to the development of low CO. However, in multivariate analysis low EF, and the fT3 concentration were the only predictors of hospital death. Conclusion: We conclude that preoperative low EF and low T3 syndrome independently causes low cardiac output and higher mortality in patients undergoing CABG. Therefore, all patients undergoing CABG should be evaluated for low T3 syndrome and patients with low T3 syndrome should be considered at increased risk. Appropriate preoperative T3 replacement therapy could decrease the postoperative complications in patients undergoing CABG. JCMS Nepal. 2015; 11(2):1-7